2008
DOI: 10.1590/s0103-50532008000200005
|View full text |Cite
|
Sign up to set email alerts
|

Meteorites: messengers from the outer space

Abstract: Milhares de meteoróides, corpos sólidos do espaço extra-terrestre, entram na atmosfera da Terra a cada ano. São pedaços de rocha, metal ou aglomerados de rocha e metal, variando em massa de frações de grama a centenas de quilogramas. Aqueles que sobrevivem à passagem através da atmosfera e caem na Terra, são chamados meteoritos. Os meteoritos são as rochas primitivas, tão antigas quanto o Sistema Solar. O estudo desses objetos enigmáticos intriga os cientistas desde tempos antigos, não apenas por seu local de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 11 publications
(16 reference statements)
0
7
0
7
Order By: Relevance
“…Now, we have about 60 years of experience in the applications of Mössbauer spectroscopy in the study of extraterrestrial materials (the first short reviews see in [9][10][11]). Then, some other reviews were published, for example, (i) concerning ideas of the solar system evolution analysis using Mössbauer spectroscopy data [12]; (ii) study of meteorites [13] and meteoritic Fe-Ni alloy [14,15]; (iii) studies of spinels in meteorites [16]; and (iv) Mössbauer spectroscopy of ordinary chondrites [17]. Further development of Mössbauer spectrometers led to appearance of new possibilities in its applications.…”
Section: Introductionmentioning
confidence: 99%
“…Now, we have about 60 years of experience in the applications of Mössbauer spectroscopy in the study of extraterrestrial materials (the first short reviews see in [9][10][11]). Then, some other reviews were published, for example, (i) concerning ideas of the solar system evolution analysis using Mössbauer spectroscopy data [12]; (ii) study of meteorites [13] and meteoritic Fe-Ni alloy [14,15]; (iii) studies of spinels in meteorites [16]; and (iv) Mössbauer spectroscopy of ordinary chondrites [17]. Further development of Mössbauer spectrometers led to appearance of new possibilities in its applications.…”
Section: Introductionmentioning
confidence: 99%
“…It is worth mentioning that a synthetic analog of tetrataenite can be prepared by a number of non-conventional methods (e.g., mechanical alloying, neutron/electron irradiation) which are known to enhance diffusion, thus allowing equilibrium to be reached in short times [9,11]. Nevertheless, comparison between the meteoritic tetrataenite and its synthetic analog produced by electron irradiation showed that in spite of similar composition, the ordering degree is much higher in meteoritic tetrataenite [13].…”
Section: Introductionmentioning
confidence: 99%
“…Іншою характерною особливістю цих стопів є те, що вони є ме-теоритними (зокрема, бразильська авторка роботи [166] називає їх «посланцями» відкритого космосу), коли склад їх становить приблизно Fe-35 ат.% Ni [166]. Детально властивості (магне-тизм, коефіцієнт термічного розширення, параметер ґратниці, електричний опір, коефіцієнт взаємної дифузії та структурні ха-рактеристики) інварних стопів Fe-Ni було розглянуто в огляді Раccеля й Гарнера [337].…”
Section: обговорення експериментальних результатівunclassified
“…Також відомо, що впорядковані й невпорядковані фази Fe-Ni з інварними (й неінварними) концентраціями було виявлено в ме-теоритних стопах (див., наприклад, [166,[349][350][351][352][353][354][355][356][357][358]). Такі метео-ритні Fe-Ni-стопи з інварними концентраціями розпадаються на (не)впорядковану ГЦК-фазу Fe 3 Ni та впорядковану фазу типу L1 0 -FeNi [359].…”
Section: обговорення експериментальних результатівunclassified